Nanoindentation of single‐crystal Bi2Te3 topological insulators grown with the Bridgman–Stockbarger method. Issue 6 (2nd February 2016) - Lamuta, Caterina; Cupolillo, Anna; Politano, Antonio; Aliev, Ziya S.; Babanly, Mahammad B.; Chulkov, Evgueni V.; Alfano, Marco; Pagnotta, Leonardo
Abstract : In this work, bismuth telluride (Bi2 Te3 ) single crystals were grown from melted polycrystalline Bi–Te material using the Bridgman–Stockbarger method. Crystalline quality and surface chemistry were investigated through X‐ray diffraction analysis and X‐ray photoelectron spectroscopy. The mechanical properties were investigated by means of depth‐sensing nanoindentation tests carried out using the continuous stiffness measurement (CSM) technique. In turn, the distribution of material hardness and Young's modulus in the depth direction (i.e., perpendicular to the single crystal basal plane) were resolved and quantitative comparisons with the available data extracted from previous literature works were drawn. It is shown that the obtained single crystals are free of contaminants and/or oxide phases and that the mechanical properties lie between those reported in recent literature for Bi2 Te3 polycrystalline thin films and 2D nanosheets.